Ice hockey players produce a unique postural sway characteristic - Walsh, M.; Slattery, E.; Haworth, J. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to examine postural sway patterns of ice hockey players and compare them with other athletes and also physically active non athletes. Balance training has become an integral part of sports training and is often included in knee injury and rehabilitation programs. We collected postural sway data for subjects during double and single legged stance for 30 seconds. The data was analyzed using traditional postural sway measures of range, length of path (or speed) as well as with Sample Entropy. Data show that ice hockey players display a different postural sway characteristic than both non athletes and American football players. This supports the idea that balance training for sport as well as rehabilitation should be designed with regards to sport specific conditions.